The Prevalence of Traumatic Brain Injury and an Investigation of Behavioural, Emotional and Executive Functioning in a Sample of Male Young Offenders - Steenkamp, Nina Simone (Department of Psychology, 2022)
Introduction: Previous research describes significant associations between criminal offending behaviour and traumatic brain injury (TBI). In young offenders, particularly, TBI is significantly more prevalent than in the general youth population. This association might be explained by the fact that key TBI sequelae (e.g., aggression, behavioural and cognitive impulsivity, emotional dysregulation) can place individuals at risk for criminal offending. However, at least two critical questions remain relatively under-investigated: Is there crossnational variability in the prevalence of TBI in young offenders and in the emotional, behavioural, and cognitive profile of young offenders with and without TBI? Few studies report on prevalence of TBI in young offender populations from low- or middle-income countries (LMICs), and fewer describe the neuropsychological profiles of TBI-afflicted young offenders from LMICs. Method: Participants were a South African sample of 25 young offenders and 56 non-offender controls. Conducting such investigations in South Africa is valuable because (a) crime rates, particularly those related to violent offences, are higher in this country than elsewhere in the world, and (b) the prevalence of TBI in South Africa is three times the global rate. All participants were administered self-report measures of emotion regulation, aggression, antisocial behaviour, as well as standardized tests of various executive functions (planning, cognitive flexibility, generative fluency, inhibition, problem solving, and rule learning/maintenance) from the Delis-Kaplan Executive Function System (D-KEFS) battery. I also gathered self-report information about their history of TBI, including whether it was accompanied by loss of consciousness (LoC). Results: Prevalence of TBI was higher in offenders (n = 18/25; 72%) than in non-offenders (n = 24/56; 43%). Offenders reported experiencing more severe TBI: The distribution of TBI with LoC was significantly different across offender and non-offender groups, p < .001. Analyses detected significant main effects of offender status on all outcomes; significant main effects of TBI on emotion regulation, aggression, and antisocial behaviour; and significant offender x TBI interaction effects on emotion regulation and aggression, ps < .036. Conclusion: These findings are broadly consistent with previous studies in this literature. Hence, the present study confirms the importance of understanding associations between TBI and offending (particularly in LMICs) and how the co-occurrence of the two is predictable and can have cumulative effects on affect, behaviour, and cognition. Because sustaining a TBI is preventable, describing the risk for negative outcomes and the socioeconomic costs thereof can inform policy development, rehabilitation planning, and initiatives to reduce recidivism rates.